Closure to "Evaluation of the potential for power-line noise to degrade real-time differential GPS messages broadcast at 283.5-325 kHz". - Silva, J.M.
The author replies to the comments made on the original paper ("Evaluation of the potential for power-line noise to degrade real-time differential GPS messages broadcast at 283.5-325 kHz", J.M. Silva, see ibid., vol.17, p.326-33, 2002) by V.L. Chartier (see ibid., vol.18, no.1, p.343, Jan. 2003).
Keywords: 283.5 kHz to 325 kHz; 283.5 to 325 kHz; EHV power lines; Electromagnetic-interference measurements; Paper discussion; Power-line noise; Real-time differential GPS messages broadcast degradation